Identitas Visual Karakter Animasi Sebagai Representasi Multikultural Labuan Bajo - Julianto, I Nyoman Larry; Mudana, I Gede; Putra Adnyana Yasa, Gede Pasek; Sustiawati, Ni Luh; Ardini, Ni Wayan; Sumerjana, Ketut; Andreani, Ni Putu Elvian (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
The visual identity of the animated characters of the Bugis, Flores and Bima tribes in Labuan Bajo is a creative manifestation of the cultural diversity that characterizes the region. Through meticulous design, these characters become strong visual representations of the rich ethnic and cultural heritage that coexists. The use of local cultural symbols, colors, and motifs provide a deep introduction to the cultural identity of each tribe, while a modern twist on the design acknowledges the changing times without sacrificing respect for tradition. This abstract discusses how the visual identity of the animated characters creates a narrative of inclusiveness and acceptance of diversity, creating an image of Labuan Bajo as a place that blends in multicultural harmony. Overall, the animated characters become a window into the beauty and complexity of the region, and contribute positively to the image of Labuan Bajo as a fascinating multicultural destination.